Intensity and isoseismal map of 25th November 2007 Delhi earthquake - PRAKASH, RAJESH; SINGH, R.K.; SHUKLA, A.K.; SINGH, D.; RANA, B.S.; JARYAL, J.S.; BHATNAGAR, A.K.; BALI, S. (MAUSAM, 2011)
An earthquake of magnitude ML: 4.3 occurred on 25th November 2007 (2312 UTC) in Delhi with hypocenter at 28.56° N / 77.08° E and focal depth 33.1 km. The epicenter was at about 21 km SW of Delhi University. It was widely felt in and around Delhi and created panic among the local populace. A macroseismic survey was conducted in about ten days starting from 27th November, 2007 at 89 locations covering an area of about 1500 sq. km in Delhi and its neighborhood through a questionnaire. The results of the macroseismic survey allowed establishment of spatial distribution of the earthquake effects in the form of isoseismal map generated using geo-statistical analysis tool of ArcGIS 9.1. The isoseismal map shows that most parts of Delhi region experienced an intensity of V on MMI scale, except on northern most region of Delhi where intensity was found IV. The mean isoseismal radii for the zones V, IV, III and II are 29.13, 57.78, 83.63 and 100.75 km, respectively. The orientation of elongated epicentral track of intensity field shows that the stress release was pronounced along Delhi-Sargodha ridge and earthquake was attributed to activities of this ridge.